2005
DOI: 10.1007/s11176-005-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio Quantum-Chemical Study of C6H5S(O)CH3 and C6H5S(O)CF3

Abstract: The potential functions of internal rotation around the C sp 23S bond in the C 6 H 5 S(O)CH 3 and C 6 H 5 S(O)CF 3 molecules were obtained by ab initio MP2(full)/6-31+G* calculations. The stationary points were identified by solving the vibrational problems. The structures in which the plane of the C sp 23S3C sp 3 bonds is approximately perpendicular to the benzene ring plane correspond to the energy minimum. The barriers to rotation around the C sp 23S bond, corrected for the zero-point vibration energy, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…28 In this respect, our results compare well with those of previous calculations. Thus, a rotational barrier of 5.1 kcal/ mol has been recently obtained by MP2/6-31G* calculations, 29 whereas a slightly higher value (8.3 kcal/mol) has been reported by Benassi et al 30 Full optimization of the geometric parameters by MP2/6-31G* calculations 29 showed that the energy minimum conformation of C 6 H 5 SOMe is reached at φ 2 ) 75°and the energy maximum at φ 2 ) 180°. Thus the preferred conformation corresponds to an SO bond nearly eclipsed with the phenyl ring as also suggested by Butenko et al 31 The conformational features of the sulfoxide appear to be slightly sensitive to the bulkiness of the alkyl group.…”
Section: Dft Calculationsmentioning
confidence: 92%
“…28 In this respect, our results compare well with those of previous calculations. Thus, a rotational barrier of 5.1 kcal/ mol has been recently obtained by MP2/6-31G* calculations, 29 whereas a slightly higher value (8.3 kcal/mol) has been reported by Benassi et al 30 Full optimization of the geometric parameters by MP2/6-31G* calculations 29 showed that the energy minimum conformation of C 6 H 5 SOMe is reached at φ 2 ) 75°and the energy maximum at φ 2 ) 180°. Thus the preferred conformation corresponds to an SO bond nearly eclipsed with the phenyl ring as also suggested by Butenko et al 31 The conformational features of the sulfoxide appear to be slightly sensitive to the bulkiness of the alkyl group.…”
Section: Dft Calculationsmentioning
confidence: 92%
“…While the stabilizing effect between a CC double bond and a carbonyl group is strongest when the p orbitals are in a collinear arrangement, X-ray crystallographic data and ab initio calculations suggest that this is not valid for SO bonds. In fact, a π bond is almost nonexistent between the S and O atoms, and the bond order is significantly smaller than 2 . Delocalization of the CC double bond into an SO bond is possible when the SO bond is approximately collinear to the π system of the CC double bond, as in the case of sulfoxides 5a − 8a .…”
mentioning
confidence: 99%
“…The main concern with this reaction is to avoid sulfone formation, which is a product from sulfoxide over oxidation. Sulfoxides possess enantiomers due to the sulfur atom as a stereocenter in a pyramidal structure (Alphand and Wohlgemuth 2010, Bzhezovsky et al 2004, Reed and Schleyer 1990, Bzhezovskii et al 2005.…”
Section: Oxidation Reactionsmentioning
confidence: 99%